Postkatastroficzne relikty i relikwie: los obrazów po Holokauście - Tippner, Anja (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The text concerns itself with the afterlife of visual representations of the victims of the Holocaust. With regard to Classe terminale du lycée chases en 1931: Castelgasse, Vienne by the French artist Christian Boltanski and drawings made by Dina Gottliebová-Babbitt in Auschwitz, questions of ownership and the appropriation are discussed. The article addresses the aporias of postcatastrophic attitudes towards the remnants of the Holocaust as well as the way in which they are treated and dealt with. The paper states, that the dynamics of dispossession, appropriation and re-appropriation that have been set into motion by the Holocaust, have not come to an end nor will they come to an end in the foreseeable future.